Glass Ionomer Subgingival Matrix Technique to Restore a Tooth with Severe Root Resorption for Implant Site Development - Ahmad Y. Imam; Raghad A. Al-Dabbagh (Hindawi Limited, 2020)
Here, we present the multidisciplinary, patient-specific management of a patient with severe external root resorption and bone loss in a maxillary anterior tooth. The tooth was provisionally noninvasively restored with glass ionomer subgingival matrix in preparation for forced orthodontic extrusion, papillary preservation, and implant placement. This approach enables clinicians to control infection within and around the resorbed tooth and then to use it as an anchor for slow forced tooth eruption to correct bone and mucogingival deformities. Aesthetic and functional outcomes were clinically and radiographically satisfactory. The advantages and disadvantages of this technique are discussed.